(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
Literacy is a complex cultural and social phenomenon with multiple effects on both, the individual and social levels. This article presents multidimensional model of literacy with linguistic, cognitive, socio-cultural, developmental and educational dimensions. A use of literacy is a literacy event and it means the use and/or presence of all dimensions of literacy. The use of new technologies and the emergence of digital literacy brought about a new meaning of literacy. There are two main processes to stress: (a) the writing (text) is more and more dominated by images and (b) the book is going to be replaced by the screen. These facts raise at least two questions: what is the future of literacy and what are psychological, social and cultural effects of these changes? The aim of this article is to present a psychological view of literacy skills with a very modest aspiration to offer a better understanding of library users and non users.